Examining the Ethical Practice of Kissing the Teacher’s Hand in Today’s Society: A Qualitative Analysis of Hadith from an Anthropological Perspective - M. Briananda Ridiansyah; Muhid; Andris Nurita (Universitas Ahmad Dahlan, 2023)
This study examines the hadith about the ethics of kissing a teacher's hand in today's society. This study uses qualitative research, emphasising literature study through the al-Jarḥ wa al-Ta'dīl method and analysis of hadith through an anthropological approach. The results of this study are the quality of the hadith about the ethics of kissing a teacher's hand in the history of Imam Abu Dawud No. 5225 status is ṣaḥīḥ. The discussion of this research reveals that in this hadith the Prophet Muhammad implicitly set an example so that Muslims always maintain relationships with other people, especially in face-to-face meetings, so as not to drown in the influence of foreign culture, negatively impacting Muslim youth. By looking at the loss of respect and obedience to elders or a form of ethics or manners that must be preserved, this study concludes that kissing the teacher's hand is something that is very much needed at this time by Muslims, especially for Muslim youths so that communication and good interpersonal relations.